Lactonase Activity, Status, and Genetic Variations of Paraoxonase 1 in Women with Gestational Diabetes Mellitus - Mi Zhou; Xing-Hui Liu; Qing-Qing Liu; Meng Chen; Huai Bai; Lin-Bo Guan; Ping Fan (Journal of Diabetes Research)
Background. Paraoxonase 1 (PON1) is a calcium-dependent multifunctional enzyme that binds to high-density lipoproteins. The physiological function of PON1 is related to its lactonase activity. However, this activity has not been analyzed in women with gestational diabetes mellitus (GDM). The present study investigated the lactonase activities and status of PON1 and their association with PON1 genetic variants and oxidative stress indices in Chinese women with GDM. Methods. This is a case-control study of 347 women with GDM and 288 women with uncomplicated pregnancies. PON1 levels and lactonase activities were analyzed using 7-O-diethylphosphoryl-3-cyano-4-methyl-7-hydroxycoumarin (DEPCyMC) and 5-thiobutyl butyrolactone (TBBL), respectively. A normalized lactonase activity (NLA) was estimated based on the ratio of TBBLase to DEPCyMCase activity. Serum malondialdehyde (MDA), total oxidant status (TOS), total antioxidant capacity (TAC) levels, and PON1 genetic polymorphisms were also analyzed. Results. PON1 lactonase activity and levels of TOS, TAC, and MDA were higher in the GDM women compared with the control women. The PON1 -108C→T genetic variation decreased the levels and lactonase activities of PON1 in a genotype-dependent manner in the patient and control groups. GDM patients with the PON1 -108TT genotype displayed lower NLA than those with the -108CC or -108CT genotype. GDM patients with the RR genotype of PON1 192Q/R polymorphism had significantly lower PON1 lactonase activities and NLA and tended to have decreased PON1 levels compared with those with the QQ or QR genotype. Multivariable regression analysis revealed that the PON1 -108C/T or 192Q/R variations, apolipoprotein (apo) A1, apoB, TAC, MDA, or age was significant predictors of the levels, lactonase activities, or NLA of PON1. Conclusions. The lactonase activities of PON1 are increased in women with GDM. PON1 genetic variants, increased oxidative stress, and abnormalities in lipoproteins may be associated with these changes.